Building resilience: a pancultural practice exploring cultures, memory & amp; modernism through hybrid and liminal condition - Pournejati, Omid (School of Architecture, Planning and Geomatics, 2022)
This dissertation draws on the experience of the third culture kid to set up a design approach for adaptive reuse. The third culture kid is someone who has lived outside of their culture/ country of origin for majority of the developing years and as a result experiences the sense of belonging or not belonging to multiple cultures to form personal identity. The Old Castle Brewery complex in Woodstock, Cape Town offers a viable site for this exploration which involves theories of isolation and integration, hybridity, and the rhizome. A connection is made between the author's Iranian Islamic culture of origin and the site through qualities of brickwork, light and courtyards.